Morphological Awareness and Its Relationship to Students’ Academic Vocabulary Knowledge - Rahim, La Ode Muhammad Nur; Tambunan, Tambunan; Rohmana, Rohmana (Journal of Teaching of English, 2021)
The objectives of this research were: (1) to find out the students’ level of morphological awareness at English Education Department; (2) to figure out the students’ level of academic vocabulary knowledge at English Education Department; (3) to see the relationship of students’ morphological awareness to students’ academic vocabulary knowledge at English Education Department. This research used correlational research design. The population was English Education Department students of Halu Oleo University who were enrolled in academic year 2020/2021 of fifth semester with a total of 127 students. The sample of this research was 32 students in class B. The research instruments were 31 questions of morphological awareness test and 32 questions of vocabulary level test (VLT) which consisted of 96 academic words. To collect the data, the researcher conducted morphological awareness test and vocabulary level test. To analyze the data, the researcher used descriptive and inferential statistics. The result of this research revealed that: (1) students’ level of morphological awareness was on low level with the mean of score is 49.39 (SD = 21.99); (2) students’ level of academic vocabulary knowledge was on low level as well with the mean of score was 54.26 (SD = 19.63); (3) based on the calculation of Pearson correlation coefficient (r) was 0.523 > critical value (0.3009), it revealed that students’ morphological awareness was significantly related to students’ academic vocabulary knowledge at English Education Department. In conclusion, the strength of the correlation of students’ morphological awareness to students’ academic vocabulary knowledge at English Education department was at moderate level (0.40 – 0.60).